Risky business: The impact of climate and climate variability on human population dynamics in Western Europe during the Last Glacial Maximum. (15th May 2017) - Burke, Ariane; Kageyama, Masa; Latombe, Guilllaume; Fasel, Marc; Vrac, Mathieu; Ramstein, Gilles; James, Patrick M.A.
Abstract: The extent to which climate change has affected the course of human evolution is an enduring question. The ability to maintain spatially extensive social networks and a fluid social structure allows human foragers to "map onto" the landscape, mitigating the impact of ecological risk and conferring resilience. But what are the limits of resilience and to which environmental variables are foraging populations sensitive? We address this question by testing the impact of a suite of environmental variables, including climate variability, on the distribution of human populations in Western Europe during the Last Glacial Maximum (LGM). Climate variability affects the distribution of plant and animal resources unpredictably, creating an element of risk for foragers for whom mobility comes at a cost. We produce a model of habitat suitability that allows us to generate predictions about the probable distribution of human populations and discuss the implications of these predictions for the structure of human populations and their social and cultural evolution during the LGM. Highlights: A new, high-resolution climate simulation for the Last Glacial Maximum is produced. Random Forests (RF) is used to select variables and produce models of human habitat suitability. Candidate variables considered in the modelling process include topographic and climate variables, as well as climate variability indices. The distribution of suitable habitat on a continental scale is predicted and its impact on human populations explored.